A concepts for calculus intervention: measuring student attitudes toward mathematics and achievement in calculus - Pilgrim, Mary, author; Gloeckner, Gene William, 1950-, advisor; Kennedy, Paul A., committee member; Dickmann, Ellyn M., committee member; Klopfenstein, Kenneth F., committee member (Colorado State University. Libraries, 2010)
Data indicate that about 40 percent of students initially enrolled in MATH 160: Calculus for Physical Scientists I finish the course with a grade of D or F, dropped, or withdrew from the course (Reinholz, 2009). The high failure rate let to an intervention course (MATH 180) for students at risk of failing MATH 160. At-risk students were identified based on their calculus exam one scores. This dissertation reports on the effect of MATH 180 during the fall 2009 semester on both student achievement in MATH 160 and math attitude. Students identified as being at-risk of failing MATH 160 were invited to drop MATH 160 and enroll in MATH 180. Not all students that were invited accepted the invitation. After completing MATH 180 during the fall 2009 semester, students then had the option to enroll in MATH 160 for the spring 2010 semester. MATH 180 students exhibited improvement in exam one scores. From the fall 2009 semester to the spring 2010 semester students raised their exam one scores by one-half of a standard deviation. Although MATH 180 students showed improvement in MATH 160 during the spring 2010 semester, there were no overall significant differences in achievement between students that took MATH 180 and those that did not. Qualitative analysis indicated that MATH 180 students came to understand that calculus problems could be solved using multiple strategies, but they did not always know what those strategies were. "In class it was hard at first to understand the direction it was going but it was helpful to try to think at math differently than I have been taught all my life." Math attitude was measured using the Modified Indiana Mathematics Belief Scales (MIMBS). MIMBS scores improved for students that took MATH 180, but there were no significant differences between MATH 180 students and non-MATH 180 students. There were significant correlations between constructs measured by the MIMBS and final course grade in MATH 160. Despite there being no significant differences in academic performance, trends in the data indicate higher final exam scores and course grades for students in the intervention group.
Keywords: success; math; concept; calculus; attitude; achievement; Calculus -- Study and teaching (Higher) -- Colorado -- Fort Collins; Academic achievement -- Colorado -- Fort Collins; Education -- Mathematics -- Colorado -- Fort Collins; Mathematics -- Study and teaching (Higher) -- Colorado -- Fort Collins